2013
DOI: 10.1016/j.neuropharm.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Selective GABAA α5 positive allosteric modulators improve cognitive function in aged rats with memory impairment

Abstract: A condition of excess activity in the hippocampal formation is observed in the aging brain and in conditions that confer additional risk during aging for Alzheimer's disease. Compounds that act as positive allosteric modulators at GABA A α5 receptors might be useful in targeting this condition because GABA A α5 receptors mediate tonic inhibition of principal neurons in the affected network. While agents to improve cognitive function in the past focused on inverse agonists, which are negative allosteric modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(117 citation statements)
references
References 50 publications
5
112
0
Order By: Relevance
“…Age-related deficits revealed by this model are associated with disrupted epigenetic regulation in the hippocampus (Castellano et al, 2012), and are sensitive to rescue by pharmacological intervention targeting a variety of mechanisms (Koh et al, 2013;. A pilot study in a small number of aged rats revealed that, consistent with results for exploratory activity in young subjects (Fig.…”
Section: Pretraining Evx Administration Fails To Ameliorate Hippocampsupporting
confidence: 62%
“…Age-related deficits revealed by this model are associated with disrupted epigenetic regulation in the hippocampus (Castellano et al, 2012), and are sensitive to rescue by pharmacological intervention targeting a variety of mechanisms (Koh et al, 2013;. A pilot study in a small number of aged rats revealed that, consistent with results for exploratory activity in young subjects (Fig.…”
Section: Pretraining Evx Administration Fails To Ameliorate Hippocampsupporting
confidence: 62%
“…As such, despite previous findings that negative modulators improve cognitive function, positive modulators that target α 5 GABA A Rs selectively are being investigated to restore hippocampal activity in aged brains. Using a rat model of age-related memory impairment, two distinct, but non-orally bioavailable, positive modulators of α 5 GABA A Rs, a benzothiophenone (compound 44) and a pyridazine (compound 6) ( Table 1, 2), considerably improved hippocampal-dependent performance tasks, while a negative allosteric modulator had no effect in any of the tasks, further supporting the use of α 5 GABA A R positive modulators in age-related memory impairment [61].…”
Section: Neurodegenerative Conditions: Alzheimer's Disease and Huntinmentioning
confidence: 83%
“…The loss of neurons in the hippocampus is partly due to the excessive stimulation of the excitatory synaptic glutamatergic receptors, which induces neuronal death [57]. Moreover, in both animal studies and neuroimaging of elderly individuals, age-related memory impairment has been shown to be associated with increased neural activity in the hippocampus [58][59][60][61]. On top of that, the number of inhibitory GABAergic interneurons in the hippocampus was found to be reduced in a mouse model that over-expresses apolipoprotein E4…”
Section: Neurodegenerative Conditions: Alzheimer's Disease and Huntinmentioning
confidence: 99%
“…And the results suggested that chronic loss of endothelial nitric oxide might be a crucial contributor to both Aβ related pathology and cognitive deficit [77]. In addition, in the investigation of the effect of GABAA α5 positive allosteric modulators on AD, RAM was used to evaluate the spatial learning and memory capacities change after dosing with these modulators [78]. Furthermore, in the study of the relation between toll-like receptor 9 signalling and AD pathology, RAM was used to test the spatial cognitive function in Tg2576 AD model transgenic mice [79].…”
Section: Ram In Novel Drug Candidate Discoveriesmentioning
confidence: 99%